Changes taking place in the proven central banking model in Poland - Paweł Sitek (Journal of Modern Science, 2021)
Objectives The purpose of the analysis is to examine the changes taking place in the proven central banking model in Poland in terms of law and in terms of changing the level of security for financial market stability in Poland, in particular the banking sector in Poland.